I am right you are wrong - "De Bono, Edward" (London, 1990)
A claim that we can now for the first time in history, begin to understand how the brain behaves as a self-organizing system in which information arranges itself into patterns. de Bono contends that logic and argument has proved very useful in dealing with technical matters but less so for dealing with human affairs. The implications of this change are spelled out in this book which suggests that humour is the most significant activity of the brain, that language is good at description but very poor on perception and that argument, the very basis of our adversarial systems, is a poor method of exchange. He also suggests that the brain is designed to set up belief systems and how our very tradition of truth and logic is only another belief system that sustains itself.
Keywords: Psychology